2015
DOI: 10.1161/strokeaha.115.010558
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Morphology Is Significantly Associated With Sex, Age, and History of Neurological Symptoms

Abstract: T he short-term risk of stroke or death of surgically treated patients having a symptomatic carotid stenosis has been shown to be similar in younger and older patients (<70 years [5.7%] versus ≥70 years [5.9%]).1 In contrast, a meta-analysis of 3 large randomized controlled trials (EVA-3S, SPACE, ICSS) revealed that the risk of stroke or death after carotid artery stenting increases significantly with age (<70 years [5.8%] versus ≥70 years [12.0%]).1 A similar trend (although not significant) has also been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 45 publications
8
50
1
3
Order By: Relevance
“…Consequently, our results show an association rather than implied causality. Also, similar to our previous study [20], we calculated odds ratios, which tend to overestimate the underlying eff ects. In addition, the estimation of plaque instability was determined according to Redgrave and Rothwell in 2008 [23], which might lead to subjective results.…”
Section: Limitationsmentioning
confidence: 59%
See 3 more Smart Citations
“…Consequently, our results show an association rather than implied causality. Also, similar to our previous study [20], we calculated odds ratios, which tend to overestimate the underlying eff ects. In addition, the estimation of plaque instability was determined according to Redgrave and Rothwell in 2008 [23], which might lead to subjective results.…”
Section: Limitationsmentioning
confidence: 59%
“…These authors analyzed 264 asymptomatic patients, focusing not directly on age or sex, but on patients with ipsilateral clinical events more than 6 months before CEA. In our recently published work [20], we analyzed patients with high-grade carotid artery stenosis using a complex multinomial regression model. Our results revealed that male sex was signifi cantly associated with infl ammation and neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eckstein wurde herausgearbeitet, dass der Nachweis einer Plaque-Hämorrhagie oder einer dünnen fibrösen Kappe (unter Berücksichtigung von Alter und Geschlecht) geeignet sein kann, Patienten mit einem erhöhten Schlaganfallrisiko zu identifizieren [15].…”
unclassified